Essential Oils: A “Potential Green” Alternative in Pharmaceutical, Nutritional and Agricultural Sectors - Nidhi Singh; Rupanshee Srivastava; Tripti Kanda; Sadhana Yadav; Rajesh Prajapati; Shivam Yadav; Kavindra Nath Tiwari; Neelam Atri (Bioactivities, 2024)
In the era of modern medicine, the therapeutic use of plant-derived essential oils has been one of the fascinating fields of study for researchers around the globe. The plant-derived essential oils, which are a combination of volatile organic compounds may be used as a substitute for the treatment of pathogenic microbes. The antimicrobial properties of essential oils are extremely diverse. In microbial infections, essential oils create an electrochemical gradient across the cell wall which intervenes with ATP synthesis and can also disrupt the electron transport system (ETS) by rupturing the mitochondrial membrane. Many essential oils have antiviral properties that can effectively treat COVID-19. The purpose of the current review is to shed light on the antimicrobial efficacy of essential oils. A survey of the methods used for the determination of the interaction and mechanisms involved in the antimicrobial activities of essential oils are also reported as well and the applications of essential oils could be interesting COVID-19 therapeutic options because of their pharmacological actions. This review will attract the attention of researchers to optimize and elucidate the use of essential oils as green alternatives to treat the deadliest infectious diseases in living organisms.